Cathepsin B-sensitive cholesteryl hemisuccinate–gemcitabine prodrug nanoparticles: enhanced cellular uptake and intracellular drug controlled release. Issue 9 (24th December 2014) - Xu, Yanyun; Geng, Jianqi; An, Ping; Xu, Yan; Huang, Jin; Lu, Wei; Liu, Shiyuan; Yu, Jiahui
Abstract : Cholesteryl hemisuccinate–gemcitabine prodrug: enhanced cellular uptake and intracellular drug controlled release. Abstract : Gemcitabine [2′, 2′-difluoro-2′-deoxycytidine (dFdC)], firstline treatment for pancreatic cancer in the clinic, is a cytotoxic nucleoside analogue. Nucleoside transporters are required in the transport of gemcitabine into cells since it is a hydrophilic compound. Actually, there are significant drawbacks for the application of gemcitabine in clinic, including a short half-life and serious side effects. In order to overcome the mentioned drawbacks, a novel prodrug, cholesteryl hemisuccinate–gemcitabine (CHSdFdC), was synthesized through covalently coupling the amino group of gemcitabine with the carboxylic group of cholesteryl hemisuccinate. The amphiphilic prodrug self-assembled spontaneously as nanoparticles in aqueous media confirmed by transmission electron microscopy (TEM). Dynamic light scattering (DLS) measurement revealed that the mean particle size is approximately 200 nm in aqueous media. The CHSdFdC nanoparticles displayed accumulative controlled drug release in simulated lysosome conditions (pH 5.0 NaAc buffer solution containing cathepsin B); the amount of drug release reached up to 80% within 10 h. However, there was almost no drug release in pH 7.4 PBS and pH 5.0 NaAc buffer solutions without cathepsin B. All these results indicated the intracellularly controlled drug release manner of the CHSdFdC nanoparticles. The controlled release of dFdC from the CHSdFdC nanoparticles was related closely to cleavage of amide bonds by cathepsin B. The CHSdFdC nanoparticles exhibited increased ability to inhibit cell growth compared with gemcitabine in vitro . Meanwhile, the CHSdFdC nanoparticles exhibited enhanced cellular uptake ability against Bxpc-3 cells, and the amount of CHSdFdC was about 15 fold of gemcitabine during the 2.5 h incubation. All these results showed that the CHSdFdC nanoparticle prodrug has great potential in the treatment of pancreatic cancer.